Measurement of Xi(++)(cc) production in pp collisions at √s=13 TeV - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Comerma-Montells, Albert; D'Argent, Philippe; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; et al. (Chinese physics. C, High energy physics and nuclear physics, 2020)
The production of baryons in proton-proton collisions at a centre-of-mass energy of is measured in the transverse-momentum range and the rapidity range . The data used in this measurement correspond to an integrated luminosity of , recorded by the LHCb experiment during 2016. The ratio of the production cross-section times the branching fraction of the decay relative to the prompt production cross-section is found to be , assuming the central value of the measured lifetime, where the first uncertainty is statistical and the second systematic.